2019
DOI: 10.1042/bsr20190612
|View full text |Cite
|
Sign up to set email alerts
|

LSINCT5 predicts unfavorable prognosis and exerts oncogenic function in osteosarcoma

Abstract: The dysregulated expression of LSINCT5 (long stress-induced non-coding transcript 5) has been found in various human tumors, and was generally related to cancer progression and unfavorable prognosis. Although the role of LSINCT5 in osteosarcoma was reported not long ago, the sample size of that study was limited. Our study presented more evidence about the clinical significance and biological function of LSINCT5 in osteosarcoma. In our results, we found LSINCT5 expression was increased in osteosarcoma tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…Previous research has shown that LSINCT5 affects the development and progression of colorectal carcinoma, ovarian cancer, 20 gastric cancer, 21 esophageal cancer, and chronic heart failure, 22,23 but there is relatively little research on OS at present. However, our study revealed that LSINCT5 was highly expressed in OS tissues and cell strains, and the 5-year survival of patients with high expression decreased, which was consistent with the study of He et al 12 However, the relevant mechanism is still unclear. Therefore, we conducted tests to further seek the potential mechanism of LSINCT5 in OS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous research has shown that LSINCT5 affects the development and progression of colorectal carcinoma, ovarian cancer, 20 gastric cancer, 21 esophageal cancer, and chronic heart failure, 22,23 but there is relatively little research on OS at present. However, our study revealed that LSINCT5 was highly expressed in OS tissues and cell strains, and the 5-year survival of patients with high expression decreased, which was consistent with the study of He et al 12 However, the relevant mechanism is still unclear. Therefore, we conducted tests to further seek the potential mechanism of LSINCT5 in OS.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have found that LSINCT5 can be used as a prognostic indicator for OS and plays a vital part in tumor carcinogenesis. 12 Nevertheless, the relevant mechanism of LSINCT5 in OS is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of long stress-induced noncoding transcript 5 (LSINCT5) were upregulated in osteosarcoma tissues and cell lines. High LSINCT5 level was positively correlated with malignant clinicopathological features, including advanced Enneking stage and histological grade, larger tumor size, and distant metastasis [ 151 ]. Besides, osteosarcoma patients with high expression of LSINCT5 showed a trend toward decreased overall survival [ 151 , 152 ].…”
Section: The Clinical Significance Of Lncrnas Involved In Wnt Pathway In Osteosarcomamentioning
confidence: 99%
“…Thus, new candidate molecules as prognostic biomarkers are expected to be developed, which may profoundly improve clinical outcomes for patients with OS. Encouragingly, some long non-coding RNAs (lncRNAs) have been reported to serve as predictive, prognostic, and therapeutic biomarkers of human cancers recently, since they are usually aberrantly expressed in disease tissues and promote or inhibit tumor development, progression, and metastasis [8][9][10][11]. Altering from the perception as 'junk' transcriptional products, lncRNAs have been recognized to play cellfunction regulatory roles and mediate cellular processes including transcription, post-transcriptional modifications, and signal transduction [12].…”
Section: Introductionmentioning
confidence: 99%